Verification of the increase in concomitant dysplasia and cancer with the size of sessile serrated lesions - Ohki, Daisuke; Tsuji, Yosuke; Hisada, Hiroyuki; Nakagawa, Hideki; Mizutani, Satoru; Oshio, Kaori; Sato, Junichi; Kubota, Dai; Cho, Rina; Miura, Yuko; Mizutani, Hiroya; Sakaguchi, Yoshiki; Takahashi, Yu; Yakabi, Seiichi; Kakushima, Naomi; Yamamichi, Nobutake; Ushiku, Tetsuo; Fujishiro, Mitsuhiro (Endoscopy International Open, 2024)
Background and study aims This study aimed to evaluate the relationship between sessile serrated lesion (SSL) size and the comorbidity rate of SSL with dysplasia (SSLD) and cancer in SSL (SSL-cancer).Patients and methods This retrospective, single-center analysis identified SSL cases that underwent endoscopic resection between January 2015 and December 2022. The prevalence of SSL, SSLD, and SSL-cancer and their annual trends were assessed. The tumor diameter was stratified as 0 to 5 mm, 6 to 9 mm, 10 to 19 mm, and ≥ 20 mm in size. Furthermore, the frequency of SSL-D/SSL-cancer was determined in each group.Results The prevalence of SSL was 2.9% (1328/45799). This prevalence was 1.8% (112/6192) in 2015 and 4.2% (230/5500) in 2022, indicating an increasing trend over time. A total of 1825 lesions were assessed: 1751 (96.0%), 55 (3.0%), 14 (0.8%), and 5 (0.3%) of lesions were SSL, SSL with low-grade dysplasia, SSL with high-grade dysplasia and SSL-cancer, respectively. Stratifying the SSLs by size: 0 to 5 mm, 5 to 9 mm, 10 to 19 mm, and ≥ 20 mm, SSLD and SSL-cancer rates were 2.3% (10/429), 2.4% (16/674), 5.3% (31/584), and 11.8% (16/136), respectively. SSLD and SSL-cancer were observed in 2.4% (26/1103) of small SSLs < 10 mm. Conclusions In cases of SSL, the rate of SSLD and SSL-cancer increased as the lesion diameter increased. A certain rate of SSLD and SSL-cancer was observed even in small SSLs less than 5mm.
Keywords: Endoscopy Upper GI Tract; Endoscopic resection (ESD, EMRc, ...); Endoscopy Lower GI Tract; Polyps / adenomas / ...; Colorectal cancer